Neurocognitive profiles in help-seeking individuals: comparison of risk for psychosis and bipolar disorder criteria. Issue 16 (17th June 2014) - Metzler, S.; Dvorsky, D.; Wyss, C.; Müller, M.; Traber-Walker, N.; Walitza, S.; Theodoridou, A.; Rössler, W.; Heekeren, K.
Abstract : Background: Neurocognitive deficits are important aspects of the schizophrenic disorders because they have a strong impact on social and vocational outcomes. We expanded on previous research by focusing on the neurocognitive profiles of persons at high risk (HR) or ultra-high risk (UHR) for schizophrenic and affective psychoses. Our main aim was to determine whether neurocognitive measures are sufficiently sensitive to predict a group affiliation based on deficits in functional domains. Method: This study included 207 help-seeking individuals identified as HR ( n  = 75), UHR ( n  = 102) or at high risk for bipolar disorder (HRBip; n  = 30), who were compared with persons comprising a matched, healthy control group (CG; n  = 50). Neuropsychological variables were sorted according to their load in a factor analysis and were compared among groups. In addition, the likelihood of group membership was estimated using logistic regression analyses. Results: The performance of HR and HRBip participants was comparable, and intermediate between the controls and UHR. The domain of processing speed was most sensitive in discriminating HR and UHR [odds ratio (OR) 0.48, 95% confidence interval (CI) 0.28–0.78, p  = 0.004] whereas learning and memory deficits predicted a conversion to schizophrenic psychosis (OR 0.47, 95% CI 0.25–0.87, p  = 0.01). Conclusions: Performances on neurocognitive tests differed among our three at-risk groups and may therefore be useful in predicting psychosis. Overall, cognition had a profound effect on the extent of general functioning and satisfaction with life for subjects at risk of psychosis. Thus, this factor should become a treatment target in itself.